Association between the triglyceride-glucose index and severe left main and/or three-vessel disease in patients with non-ST-segment elevation myocardial infarction: a dual-centre retrospective study - Shaoyuan Chen; Peiyi Xie; Xueying Han; Yulian Huang; Dongdong Chen; Haigang Zhang; Bihan Huang (BMJ Open)
Objective This study aimed to investigate the relationship between the triglyceride-glucose (TyG) index and the presence of severe left main and/or three-vessel disease (LM/3VD) evaluated by SYNTAX score.Design Cross-sectional study.Setting Shenzhen Nanshan People’s Hospital and The First Affiliated Hospital of Jinan University.Participants 596 patients were first diagnosed with non-ST-segment elevation myocardial infarction (NSTEMI).Primary outcome measures Incidence of severe LM/3VD and the relations between the TyG index and the severe LM/3VD evaluated by SYNTAX score.Results After fully adjusting for confounders, the TyG index was a significant independent predictor for severe coronary artery disease (CAD) (OR 1.744; 95% CI 1.166 to 2.609; p 0.007). The TyG and severe CAD were found to be linearly correlated using the restricted cubic splines (p for non-linearity=0.161). The TyG demonstrated a consistent association with severe CAD across different subgroups, such as individuals with and without diabetes, hypertension, hyperlipidaemia and different haemoglobin (<6.5 or ≥6.5). No statistically significant interaction was detected within the subgroup (p > 0.05). In comparison to risk factors based solely on age or ST-elevation in lead Augmented Unipolar Right-arm (aVR), the area under the curve value for the prediction of severe CAD was modestly improved to 0.759 by the addition of the TyG.Conclusion Patients with NSTEMI demonstrated that a positive relationship was found between a higher level of TyG and an increased level of coronary anatomical complexity (LM/3VD with SYNTAX score >22). The TyG could serve as a non-invasive marker for predicting severe CAD and have implications for guiding treatment strategies in patients with NSTEMI.